Implication of dividend policy on share price: a panel study / Nor Hidayati Md Khalid - Md Khalid, Nor hidayati (2016)
This issue is exists due to the stock price reactions towards the dividend policy in the plantation sector of Malaysia. Dividend policy has been debated by the analyst which is stated that it play an important role to determine the share price of the company. This research will be explained the result of the effects on the dividend policies toward the plantation sector by using the financial element ratio which is involve the dividend yield, dividend pay-out, retained earnings, and earning per share and also involve in the total liabilities of the company. In this study the sample is collected by yearly basis from period 2008 to 2014. The method that be conducted based on the secondary data which is obtain from the Thomson Reuters DataStream for the 7 years. It is involved data from 12 plantation companies out of 45 companies in the industry which are included each of independent variables such as dividend yield, dividend pay-out, total liabilities, retained earnings, and earning per share